EXCAVATION DATA AND FAILURE INVESTIGATION ALONG TUNNEL OF SYMBOL MOUNTAIN - Chatziangelou M., Chatziangelou M.; Thomopoulos, Ach.; Christaras, B. (Bulletin of the Geological Society of Greece, 2010)
The tunnel of Symbol Mountain, which is 1160m long, is placed on South-west of Kavala City at Northern Greece. The tunnel consists of two bores with NW-SE direction, which are connected with two small tunnels. The stability of the rock mass was limited, during the excavation, because the rock mass was often changing, the faults are open, and the aquifer is placed above the excavation. The aim of the present paper is to describe the dangerous geological status of Symbol Mountain and to propose excavation solutions of the unexpected failure conditions. For the above reasons, the sudden changes of the rock mass quality along the tunnel excavation are described. The causes of the geological failures were investigated and the failures were classified. Furthermore, the efficacy of support measures was tested and a relationship between the apparent face of wedges and the shotcrete thickness was proposed.